Evaluation and refinement of zinc management options for field-specific nutrient management in eastern India - Mishra, Ajay Kumar; Padbhushan, Rajeev; Bharti, Preeti; Sharma, Sheetal; Patnaik, Girija Prasad (Springer, 2025)
In eastern India, zinc (Zn) has emerged as the most critical micronutrient impacting the yield of rice. Experiments were conducted for 2 years during the Rabi and Kharif rice seasons at 339 on-farm locations in five districts and four agroclimatic zones of Odisha state in eastern India to study the management of Zn in rice nurseries and the transplanted crop. At each location, five treatment plots were established in which nitrogen (N), phosphorus (P) and potassium (K) were applied to rice following site-specific nutrient management as guided by Rice Crop Manager (RCM), a web-based tool. In the three treatments, the rice nursery was treated with compost (4 t ha-1) or 50 or 100 kg Zn sulfate ha−1 (on a nursery basis), while the transplanted crop was supplied with only N, P, and K. In the remaining two treatments, no compost or Zn was applied to the rice nursery, but 12.5 or 25 kg Zn sulfate ha−1 was applied along with N, P, and K to the transplanted crop. Rice grain yield, system yield, and gross return above fertilizer cost (GRF) were significantly greater (p < 0.05) with the application of 50 kg Zn sulfate ha−1 than with the application of compost (farmer practices) to rice nurseries. Applying 100 kg Zn sulfate ha⁻1 to the nursery or 12.5–25 kg Zn sulfate ha⁻1 to transplanted rice did not increase yield or GRF. Higher yield, grain Zn content, and GHG emissions occurred in the Rabi season, with the lowest GHG emissions recorded when the nursery received 100 kg Zn sulfate ha⁻1 in both seasons. The results of this study convincingly prove the usefulness of applying Zn along with site specific nutrient management (SSNM) in rice in eastern India to produce high yields and GRFs and reduce GHG emissions.